Efektivitas Gamifikasi terhadap Keterlibatan Siswa dalam Pembelajaran Daring : Systematic Literatur Review - Salim, Ahkamsyadid Yusmaputra; Rani, Shaumi; Sayidaturrahmah, Sitti Saum; Kesuma, Dany Wijaya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The problem faced in online learning is the low student engagement, which can affect their learning outcomes. Gamification, as an innovative approach, is expected to improve student motivation and participation in the online learning environment. This study aims to review the effects of gamification on student engagement, focusing on intrinsic and extrinsic motivation during online learning. The method used is a systematic review of articles relevant to this topic. The article review process involves examining studies that identify various elements of gamification, such as incentives, competition, collaboration, and formative assessment, and their impact on student engagement and motivation. The expected result of this research is to provide insights into how gamification can enhance student engagement, as well as to identify the most effective gamification elements in the context of online learning. Additionally, this study aims to offer practical recommendations for educators on how to implement gamification to improve learning effectiveness.